Chylomicron retention disease in a 2-year-old girl with a novel deletion in the SAR1b gene: A case report and literature review - Ibrahim, Judy; Zaabi, Nuha Al; Hertecant, Jozef (Indian Journal of Child Health, 2018)
Chylomicron retention disease (CMRD) is a rare disorder of lipid absorption, and its prevalence is <1/million. It is an autosomal recessive disorder with a genetic mutation in the SAR1B gene. We report a case of a girl who had the typical symptoms in the early infancy, in whom CMRD was strongly suspected clinically and due to the endoscopy findings. Unfortunately, the treatment was delayed, waiting for genetic confirmation, which was not available in her country. When we first saw the patient at the age of 2 years, she had severe failure to thrive. She recovered very fast with a trial of a fat-restricted diet and medium chain fatty acid supplementation. The working diagnosis of CMRD was later confirmed genetically. We conclude that a therapeutic trial is essential in this type of disease once the diagnosis is suspected to avoid further damage to the patient. This applies especially to resource-restricted environments.